Konsep Primitif Dan Makna Pada Ilustrasi Desain T-Shirt Lombok - Putri, I Gusti Ayu Agung Aristi; Rusdin, Febi Ramadhani; Ayu, Ilmi Sila (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to understand how primitive concepts are applied to the illustration of Lombok t-shirt designs and the meanings contained within these designs. The research employs both primary and secondary data collection methods. Primary data, which supports the research, is obtained from field studies and interviews. Secondary data is gathered from various sources, including books, scientific journals, research reports, and other library sources. The results of this research reveal that through the analysis of visual elements, the Lombok t-shirt design incorporates primitive concepts. The illustrations predominantly feature curved lines, and the color palette is limited, with a dominant use of blue. The signs present in the Lombok t-shirt designs convey both denotative and connotative meanings.